ENT600: Safety vest / Muhammad Hazim Ismail, Danial Syaraani Ramlan and Ahmad Niza Md Yassin. - Ismail, Muhammad Hazim; Ramlan, Danial Syaraani; Md Yassin, Ahmad Niza (2018)
Law enforcement officers are empowered with the awesome responsibility and authority to maintain public order. At the same time, officers have the unique opportunity to engage with citizens, identify and solve problems, and positively affect their communities on a daily basis. The result is a dynamic profession that blends tactical response, critical thinking, and interpersonal skill. Law enforcement agencies respond to tens of thousands of calls for service each year. Each day presents new challenges that require application of these varied skills in new and different situations. The goal of this project is to develop and study a device that can detect pressure and send the data over a wireless transmission. Wireless hands-free technology is rapidly adapting to a variety of technology today. The purpose of this project was to take the "Officer Down" protocol and simplify it into a device that handles the procedure without user input. The solution was a body vest that is worn under the current equipment and detects harmful attacks. It then reports these attacks back to the station. Currently, the police use a button attached to the belt to alert the dispatcher if there is a problem. However there may be situations in which the officer becomes incapacitated or unable to alert the proper channels. It is possible to design sensors and equipment that will make the users that much safer. Various materials needed to be researched to determine which would be best suited for the device. The goal is to build a device that would detect an impact inflicted onto the vest which would then transmit the signal to an on board computer, and further sends that information to the dispatcher. Once the dispatcher takes hold of the signal, they can use proper protocol to ensure the safety of the officer. One of the major pieces of the device is the sensor. It is designed to be flexible and detect certain impacts. The sensor monitors a variable capacitance, and once the threshold is reached, the signal is sent over to the transmitter. The transmitter needs to be low power and mobile as the officer needs to be able to walk where he needs to and not worry about being attached to the car. A proper receiver would then be determined signals that may interfere. This project details how the blocks mentioned come together to meet the device requirements. In the end we were able to successfully construct the device, though we had some issues.